h.hofstede (h.hofstede@hogeland.nl)

       
1. a. Q = S(1 + pt)
Q = S + Spt
Spt = Q - S
p = (Q - S)/St
 
       
  b. V = q (2/a - 5pR/m)
V = 2q/a - 5pqR/m
5pqR/m = 2q/a - V
R = m/5pq (2q/a - V)
 
       
  c. 1/v + 1/b = 1/f 
1/b = 1/f - 1/v = v/fv - f/fv = (v - f)/fv
b = fv /
(v - f) 
 
       
  d.  z = 4/(2p - 3) 
(2p - 3)z = 4
2pz - 3z = 4
2pz = 4 + 3z
p
= (4 + 3z)/2z  = 2/z + 1,5
 
       
  e.  y = (2x - 4)/(4x + 1)
y(4x + 1) = 2x - 4
4xy + y = 2x - 4
4xy - 2x = -y - 4
x(4y - 2) = -y - 4
x = (-y - 2)/(4y - 2) = (y + 2)/(4 - 4y)
 
       
2. a.   y = √(2/x) + 4.
y - 4 = √(2/x)
(y - 4)2 = 2/x
x
(y - 4)2 = 2
x = 2/(y - 4)
 
       
  b. (b + 1)/(√(1 - a)) = b.
b + 1 = b √(1 - a)
√(1 - a) = (b + 1)/b = 1 + 1/b
1 - a = (1 + 1/b)2
1  - (1 + 1/b)2 = a

toegift:
a
= 1 - 1 - 2/b - 1/b2
a = -2/b - 1/b2 
 
       

h.hofstede (h.hofstede@hogeland.nl)